PEMANFAATAN TEKNOLOGI AUGMENTED REALITY VIDEO EMBEDDED DALAM PENGENALAN DESTINASI WISATA MAJALENGKA SEBAGAI MEDIA INFORMASI - Nur'aeni , Rohimatun; Prasetyo , Tri Ferga; Budiman (Universitas Majalengka, 2025)
This study examines the use of Augmented Reality (AR) technology with embedded video as an innovative medium for introducing tourism destinations in Majalengka Regency. The application was developed using a marker-based AR approach, enabling users to access tourism information in the form of text, images, and videos through their mobile devices. Data were collected through observation and documentation of local attractions, while system development focused on enhancing interactivity and usability. Testing results show that AR with embedded video not only provides a more engaging and immersive experience compared to conventional promotional media but also improves the clarity and attractiveness of tourism information delivery. The findings highlight that this technology can effectively function as both an information and promotional tool, supporting regional tourism development initiatives and encouraging greater tourist interest in visiting Majalengka.